Aurantio-obtusin induces hepatotoxicity through activation of NLRP3 inflammasome signaling. (1st January 2022) - Hu, Manjiang; Lin, Li; Liu, Jun; Zhong, Yizhou; Liang, Boxuan; Huang, Yuji; Li, Zhiming; Lin, Xi; Wang, Bo; Zhang, Bingli; Meng, Hao; Ye, Rongyi; et al.
Highlights: AO delays yolk sac absorption, and increases liver area and inflammation in larval zebrafish. AO is quickly absorbed into the blood and rapidly metabolized in mice. AO induces hepatotoxicity in a gender-dependent manner in mice. AO induces liver dysfunction, hepatocyte necrosis with inflammation in female mice. AO activates NLRP3 inflammasome signaling via increasing KCNN4 and ROS and inhibiting NF-κB. Abstract: Aurantio-obtusin (AO) is a major anthraquinone (AQ) compound derived from Cassiae semen (CS). Although pharmacological studies have shown that the CS extracts can serve as effective agents in preclinical and clinical practice, AQ-induced hepatotoxicity in humans has attracted widespread attention. To explore whether AO induces hepatotoxicity and its underlying mechanisms, we exposed larval zebrafish and mice to AO. We found that AO delayed yolk sac absorption, and increased liver area and inflammation in the larval zebrafish. This inflammation was manifested as an increase in liver neutrophils and the up-regulated mRNA expression of interleukin-6 ( Il-6 ) and tumor necrosis factor -α ( Tnf-α ) in the larval zebrafish. Furthermore, a pharmacokinetics study showed that AO was quickly absorbed into the blood and rapidly metabolized in the mice. Of note, AO induced hepatotoxicity in a gender-dependent manner, characterized by liver dysfunction, increased hepatocyte necrosis with inflammatory infiltration, and up-regulated mRNAs of Il-6, Tnf-α and monocyte chemotactic protein 1( Mcp1 ) in the female mice after 28-day oral administration. It also highlighted that AO triggered NOD-like receptor protein (NLRP) signaling in the female mice, as evidenced by the increased NLRP3, Caspase-1, pro-IL-1β, IL-1β and IL-18. Finally, we found that AO led to a significant increase in potassium calcium-activated channel, subfamily N, member 4 (KCNN4) and reactive oxygen species (ROS) levels, along with decreased nuclear factor kappa B p65 (NF-κB p65), in the female mouse livers. In conclusion, AO induced hepatotoxicity by activating NLRP3 inflammasome signaling, at least in part, through increased KCNN4 and ROS production, and NF-κB inhibition.